CEO Foreign Experience and Green Innovation: Evidence from China - Quan, Xiaofeng; Ke, Yun; Qian, Yuting; Zhang, Yao (Journal of business ethics, 2023)
We examine whether and how CEO foreign experience affects firm’s green innovation. Using a sample of Chinese public companies and hand-collected CEO foreign experience data, we document a positive association between CEO foreign experience and corporate green innovation. Furthermore, consistent with the view that CEOs with foreign experience would play a more significant role when provided with more resources, we find that the positive relationship is more pronounced in less financially constrained firms, in state-owned enterprises, and in less competitive industries. Additional analyses indicate that enhanced environmental ethics and general competency are two potential mechanisms through which CEO foreign experience affects corporate green innovation. Finally, we find that CEO foreign experience is positively related to green innovation quality and internationalization. Collectively, these findings suggest that CEO foreign experience is a significant factor for corporate green innovation in emerging markets.